Pengaruh Pemanfaatan Smartphone Terhadap Hasil Belajar Ekonomi Studi Kasus Pada Masa Pandemi Covid-19 Di SMA Srijaya Negara Palembang - Leman Arahab; Erma Yulaini; Nova Pratiwi (Universitas Nusantara PGRI Kediri, 2022)
The problem in this study is whether there is an effect of smartphone use on student learning outcomes at SMA Srijaya Negara Palembang. The purpose of this study was to determine whether there was an influence of smartphones on economic learning outcomes during the COVID-19 pandemic at Srijaya Negara Palembang High School. The research method used is descriptive quantitative method. And for data analysis used is questionnaire data analysis, questionnaire data analysis, normality test, linearity test, simple regression test, calculation of the coefficient of determination and t test with a population of class XI IPS, sampling is done by sampling saturated is a sampling technique if all population members are used as samples. The sample is part of the population that has relatively the same characteristics and is considered to be representative of the population so that as many as 60 students are obtained. Data collection techniques used are questionnaires and documentation. Based on the discussion of the research results, the use of smartphones is categorized as having a good positive impact on students of SMA Srijaya Negara Palembang in the 2021/2022 academic year of 77.12 in the Strong category. Enough